Design of Qirâ`ah Skill Learning Media Based on The Book Creator Application - Rahman, Very Aulia; Sutiah, Sutiah; Machmudah, Umi; Adam, Faisal Mahmoud (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
The Book Creator application has become one of the most relevant and modern learning media for teaching mahârah qirâ`ah. This study aims to develop a Book Creator-based learning medium and evaluate its effectiveness in nahârah qirâ`ah instruction. This research follows a Research and Development (RnD) approach using the ADDIE design model, developed by Reiser and Mollenda. Through the ADDIE stages—Analysis, Design, Development, Implementation, and Evaluation—this study explores students' learning needs, the implementation of the product, and the evaluation of the Book Creator-based learning tool. The evaluation of mahârah qirâ`ah learning through this application is based on several assessment indicators, including word meaning acquisition, coherence between sentences, general comprehension with appropriate grammatical accuracy (qawâ’id), and understanding of the text’s message. A key indicator of effective learning is students’ ability to analyze reading texts and articulate their understanding in their own words. Moreover, Book Creator serves as a tool that enhances students’ enthusiasm for learning Arabic.